Two layers of graduated compression stockings can reduce healthy saphenous vein diameters in the standing position. (September 2019) - Yang, Anes; Yasaman, Bahar; Parsi, Yana; Kang, Mina; Connor, David; Parsi, Kurosh
Background: Previous studies reported graduated compression stockings can reduce the calibre of deep veins in the standing subjects. However, the literature has been inconclusive on the effect of graduated compression stockings on superficial veins in standing subjects. Objectives: To assess the effect of two layers of graduated compression stockings on the diameter of saphenous veins in healthy subjects. Materials and methods: In 17 legs of nine healthy subjects, we studied the effect of single layering and double layering of graduated compression stockings (23–32 mmHg, Thigh High Belted Sigvaris, Switzerland) on the diameter of the great saphenous vein mid-thigh, great saphenous vein mid-calf and small saphenous vein mid-calf. The measurements were taken using duplex ultrasound (Toshiba Aplio XG 500, 18-7 MHz transducer), through the fabric using a generous amount of ultrasound gel, on subjects both supine or prone and standing. Results: Two layers of Class II graduated compression stockings reduced the calibre of great saphenous vein mid-thigh from (4.1 mm to 3.3 mm, p < 0.05), great saphenous vein mid-calf (2.8 mm to 2.2 mm, p < 0.01) and small saphenous vein (2.7 mm to 1.9 mm, p < 0.01) in the standing position. In the supine or prone position, great saphenous vein showed narrowing but there was no measurable change in the calibre of the small saphenous vein. The degree of narrowing was measurable, but insufficient to approximate the vein walls. Conclusion: Superimposition of two Class II graduated compression stockings reduced the calibre of the saphenous veins in the standing position but did not approximate the vein walls. In the supine or prone position, the addition of a second layer of graduated compression stockings did not result in further narrowing of the saphenous veins.